2022
DOI: 10.33757/jik.v6i1.480
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian Ikutan Pasca Imunisasi (KIPI) Vaksin Covid-19 Dosis Pertama dan Kedua

Abstract: Vaksinasi merupakan upaya pencegahan Covid-19. Vaksin Covid-19 masih tergolong baru dan masyarakat masih merasa takut terjadinya kejadian ikutan pasca imunisasi (KIPI). Untuk meningkatkan partisipasi masyarakat melakukan vaksinasi maka KIPI vaksin Covid-19 perlu dievaluasi. Tujuan penelitian adalah mengetahui perbandingan KIPI vaksin Covid-19 dosis pertama dan kedua. Jenis penelitian adalah penelitian deskriptif kuantitatif. Pengumpulan data menggunakan kuesioner adverse events following immunisation. Jumlah s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…[28] Research by Desnita et al (2022) in Padang using 95 samples obtained similar results where the most common COVID-19 vaccine AEFI symptom in the local reaction group was pain at the injection site which was experienced by 70 people (73,70%) after the first primary dose vaccination and 65 people (69,00%) after second primary dose vaccination. [27] The research results by Volume 10; Issue: 12; December 2023 Supangat et al (2021) in Jember also showed that the most common local symptom of AEFI was pain at the injection which was experienced by 25 people (45%) after the first primary dose vaccination and 34 people (67%) after second primary dose vaccination. [31] Pain at the injection site arises because of vaccine liquid being injected intramuscularly, which can stretch the muscle fibers, thereby triggering an immune reaction in the form of inflammation.…”
Section: Aefi Of Covid-19 Vaccine In Balimentioning
confidence: 67%
See 1 more Smart Citation
“…[28] Research by Desnita et al (2022) in Padang using 95 samples obtained similar results where the most common COVID-19 vaccine AEFI symptom in the local reaction group was pain at the injection site which was experienced by 70 people (73,70%) after the first primary dose vaccination and 65 people (69,00%) after second primary dose vaccination. [27] The research results by Volume 10; Issue: 12; December 2023 Supangat et al (2021) in Jember also showed that the most common local symptom of AEFI was pain at the injection which was experienced by 25 people (45%) after the first primary dose vaccination and 34 people (67%) after second primary dose vaccination. [31] Pain at the injection site arises because of vaccine liquid being injected intramuscularly, which can stretch the muscle fibers, thereby triggering an immune reaction in the form of inflammation.…”
Section: Aefi Of Covid-19 Vaccine In Balimentioning
confidence: 67%
“…Based on the data obtained, most COVID-19 vaccine AEFI cases were reported from hospitals with 511 cases (53,34%), followed by primary health care (puskesmas) with 198 cases (20,67%), and immunization centers with 131 cases (13,67%) (Table 4). [27] Another study by Riad et al (2021) stated that the most frequent AEFI that appeared after Sinovac vaccination were pain at the site of injection, fatigue, headaches, myalgia, and arthralgia with higher symptoms incidence in women (p < 0,001). [28] The higher number of AEFI reports after the Sinovac vaccination can also be related to the number of Sinovac doses used which dominates in Indonesia considering that Sinovac was the first COVID-19 vaccine that is permitted in Indonesia so the chance of AEFI incidence is higher.…”
Section: Aefi Of Covid-19 Vaccine In Balimentioning
confidence: 98%
“…Gejala lesu atau kelelahan yang terjadi dosis pertama dilaporkan lebih tinggi daripada dosis kedua dimana sebesar 10,1 % (81 orang) yang terjadi pada vaksinasi dosis pertama dan pada dosis kedua 8,3 % (67 orang), hal ini sesuai dengan penelitian Desnita et al (2022) dimana pada dosis pertama sebanyak 9,5% responden sedangkan pada dosis kedua sebanyak 4,7% responden. Keluhan sakit disertai kelemahan pada lengan yang disuntik pada dosis pertama dilaporkan sebesar 8,8 % (71 orang) dimana angkanya lebih tinggi dibandingkan pada dosis kedua yaitu 8,6 % (69 orang), penelitian yang dilakukan oleh Simanjorang et al (2022) diperoleh keluhan pada dosis pertama sebesar 4,8% dan angkanya menurun pada dosis kedua yaitu 4,1%.…”
Section: Hasil Dan Pembahasan Karakteristik Respondenunclassified
“…2 Tantangan dalam vaksinasi COVID-19 adalah kejadian ikutan pasca imunisasi (KIPI). Penelitian yang dilaksanakan di Kota Padang didapatkan bahwa reaksi KIPI terbanyak adalah 60,7% mengalami nyeri pada area suntikan, 47,1 % mengalami kelelahan namun tidak mengganggu aktivitas sehari-hari, dan 29,4% responden mengalami sakit kepala (Desnita et al, 2022). Penelitian di Kota Makassar mendapatkan bahwa KIPI terbanyak adalah reaksi lokal yaitu nyeri pada lokasi suntikan sebanyak 98% di dosis pertama dan 95,3% di dosis kedua.…”
unclassified
“…Tenaga kesehatan yang paling banyak mengalami KIPI adalah profesi perawat (38%) (Romadhan et al, 2022). Penelitian sebelumnya didapatkan jumlah tenaga kesehatan yang mendapatkan KIPI vaksin COVID-19 sebagian besar tidak memiliki riwayat komorbid (98,9%) dan didapatkan tidak terdapat hubungan antara komorbid dengan KIPI vaksin COVID-19 (Desnita et al, 2022).…”
unclassified